Compact Right-Handed Circularly Polarized V-Shaped Patch Array Antenna for Nanosatellites - Haider Ali; Dawar Awan; Inam Bari; Wajahat Ullah Khan Tareen; Umar Farooq Khattak; Nikita Goel; Manish Varun Yadav (Journal of Electrical and Computer Engineering)
Nanosatellites have opened up significant opportunities for small and medium enterprises and academic institutions in space technology, driving demand for compact, high-performance antennas. This study presents a miniaturized, right-handed circularly polarized (RHCP) V-shaped patch array antenna, integrated with a matched feeding network, tailored for nanosatellite applications. The innovative design achieves a compact 13 × 13 cm2 footprint while delivering a high gain of 8.95 dBi, a wide −3 dB beamwidth of 55°, and an axial ratio (AR) of less than 5 dB over a 61° beamwidth. A −10-dB return loss (RL) bandwidth of 80 MHz at 2.45 GHz ensures reliable performance within the S-band. The proposed design offers significant advantages over traditional antennas, including enhanced polarization stability and efficient communication links under orientation shifts, making it ideal for telemetry, tracking, control (TT&C); Earth observation; and remote sensing missions in nanosatellites. These results highlight the antenna’s potential to advance satellite communication systems in compact and constrained environments.